The Role of Digital Health Under Taiwan's National Health Insurance System: Progress and Challenges - Jui-Fen Rachel Lu; Li-Lin Liang (Taylor & Francis Group, 2024)
Digital health covers a wide spectrum of applications of digital technologies in the healthcare field. As a new set of tools to support the health system in achieving its goals-improving access to care, quality of care, and system efficiency-digital health has significantly transformed the landscape of modern medicine and health care. This paper examines the role of digital health under Taiwan National Health Insurance, considering the profound impacts of digital health during the COVID-19 pandemic. It focuses specifically on big data management and analytics (MediCloud and My Health Bank/NHI Mobile Easy Access) and innovative service provision models (telemedicine). We discuss two imminent challenges that any health system is likely to encounter: digital trust and digital divide. For the digital divide, we assessed the use of telemedicine and its determinants during the COVID-19 pandemic. Our study shows that high-income levels and the presence of chronic or severe illness were positively correlated with the use of telemedicine. This observation suggests that poor people who have poorer health status were most likely to suffer from unmet needs for telemedicine. Enhancing cybersecurity to safeguard confidentiality, and effective communications with the public are fundamental and essential steps to regaining public trust in the digital era. When calling for more investment in digital technology, policy makers should be mindful of the potential digital divide across the demographic and socioeconomic strata, and specific policies should be devised to provide support to target the socially disadvantaged group.